Implementation of Article 1666 of the Civil Code on House Disputes Granted by a Person to a Non-Heir - Lia Fazira; Kusno Kusno; Risdalina Risdalina (International Journal Labs, 2023)
The definition of a grant is contained in Article 1666 of the Penal Code, which is an agreement by which a grantor gives up an item free of charge, without being able to withdraw it, for the benefit of a person who accepts the delivery of the goods. This study aims to find out and analyze about giving grants to someone who is not an heir. As well as knowing and analyzing about dispute resolution about granting grants to someone who is not an heir. This research belongs to the normative type of research. So it can be seen that the granting of a grant to a person who is not an heir is permissible, with the requirement that there is the consent of the heirs and cannot be more than 1/3 of the existing estate. In addition, the settlement of disputes regarding the granting of grants to a person who is not the heir is the heir may sue again for the grant if in the grant the grant exceeds 1/3 of the estate, other than because it does not first fulfill the legitime portie to the heirs.